2019
DOI: 10.21037/tcr.2019.05.30
|View full text |Cite
|
Sign up to set email alerts
|

The impact of neighborhood disadvantage on health-related quality of life among African American and White cancer survivors

Abstract: Following improvements in cancer survival rates quality of life (QOL) has become a key health outcome among cancer survivors. Neighborhood disadvantage has been shown to have a detrimental effect on health outcomes. To date, little is known regarding the influence of neighborhood disadvantage on the health-related QOL of cancer survivors. This study aimed to examine the associations between neighborhood disadvantage and health-related QOL among African American and White cancer survivors. Data were obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Evidence supports the critical role of rehabilitation, exercise, emotional and nutritional support in maximizing quality of life during and after treatment [16]. Barriers to rehabilitation and recovery care exist for all BC survivors but are magnified in Black survivors due to systemic racism, healthcare provider bias and discrimination, lack of culturally relevant care models, and socio-economic barriers [17].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence supports the critical role of rehabilitation, exercise, emotional and nutritional support in maximizing quality of life during and after treatment [16]. Barriers to rehabilitation and recovery care exist for all BC survivors but are magnified in Black survivors due to systemic racism, healthcare provider bias and discrimination, lack of culturally relevant care models, and socio-economic barriers [17].…”
Section: Introductionmentioning
confidence: 99%
“…Population-based, large-scale studies among adult patients in the general population with chronic health conditions or survivors of adult-onset cancers show poorer self-rated health and HRQOL among those living in deprived areas compared to those living in non-deprived areas [21,40], though the evidence in survivors of childhood cancer is limited. In this study, we found that living in counties deemed as deprived due to SES and physical environmental circumstances is linked to psychological stress, fatigue, and sleep disturbances, as well as diminished positive affect and mobility among young cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, greater neighborhood stress was associated with poorer self-reported health in a study examining neighborhood context and health outcomes among urban Black women and English-and Spanish-speaking Latina women with breast cancer [26]. Further, neighborhood characteristics such as neighborhood socioeconomic status racial/ethnic composition, population density, and degree of urbanicity have been shown to affect HRQL among various cancer survivors [44][45][46].…”
Section: Discussionmentioning
confidence: 99%